2015
DOI: 10.3892/ijo.2015.2970
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma brain metastases: Treatment results and prognostic factors - a single-center retrospective study

Abstract: Abstract. The brain is one of the most frequent locations of metastasis in malignant melanoma. We aimed to identify prognostic factors for overall survival (OS) and local tumor control (LC) in patients with malignant melanoma metastasized to the brain treated by multimodal therapy. All patients diagnosed with malignant melanoma brain metastases between 1992 and 2011 at a single center were registered (n=100, 65% male, 35% female). OS and LC of individual brain metastases were retrospectively analyzed. Subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…Although other studies [8,25] found that NM histologic type was associated with BM development, we did not see this when corrected for tumor depth. Our patients with BM were predominantly male, as seen in other studies [8,12,17,26], although our stage-matched control group was similarly male-predominant. A review of multiple studies concluded that male patients with BM have a poorer prognosis [18], although we did not address that issue here.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although other studies [8,25] found that NM histologic type was associated with BM development, we did not see this when corrected for tumor depth. Our patients with BM were predominantly male, as seen in other studies [8,12,17,26], although our stage-matched control group was similarly male-predominant. A review of multiple studies concluded that male patients with BM have a poorer prognosis [18], although we did not address that issue here.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, we were able to confirm development of stage IV disease in only 10/237 (8.4%) of our control patients and lack of distant metastasis in only 79/237 (33.3%); for the remainder of our control patients (100/237, 42.2%), we did not have recent follow-up to ascertain this information. In reviewing the literature, we note that of nine studies examining melanoma BM, four had no control group [4,12,26,29], four had a control group similarly constructed as ours [5,6,8,9], and only one had a control group with non-brain distant metastasis [10]. …”
Section: Discussionmentioning
confidence: 99%
“…However, this is in line with previously published data. In the cohort of Ostheimer et al, the reported median OS times for patients with multiple BM from MM were around 2.5 months despite systemic and local treatment and as short as 1.5 months with best supportive care only 29. In a recent analysis by Frinton et al, OS was 4.8 months from the diagnosis of BM and 2.2 months in patients receiving WBRT only 30.…”
Section: Discussionmentioning
confidence: 98%
“…Many drugs (e.g., fotemustine and temozolomide) are not effective for the treatment of melanoma with brain metastasis due to the blood–brain barrier. [ 7 ] With emerging studies of immune checkpoint inhibitors (anti-CTLA-4/anti-PD1), immunotherapy has brought hope to MBM patients. Clinical trials have proven the efficacy of ipilimumab (the CTLA-4 inhibitor), with reported central nervous system control rates of 16–65% and median OS times of 2.5 to 29.3 months, grade 3 to 4 toxicity was 6 to 44.7% (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%